2006
DOI: 10.2215/cjn.00850805
|View full text |Cite
|
Sign up to set email alerts
|

Early Arteriovenous Fistula Failure

Abstract: A significant number of arteriovenous fistulae (28 to 53%) never mature to support dialysis. Often, renal physicians and surgeons wait for up to 6 months and even longer hoping that the arteriovenous fistula (AVF) will eventually grow to support dialysis before declaring that the AVF has failed. In the interim, if dialysis is needed, then a tunneled catheter is inserted, exposing the patient to the morbidity and mortality associated with the use of this device. In general, a blood flow of 500 ml/min and a diam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
219
2
9

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 260 publications
(236 citation statements)
references
References 45 publications
(63 reference statements)
6
219
2
9
Order By: Relevance
“…Most experts advocate early placement of AVFs considering that fistulae need about 4-6 weeks to mature for use, 20,21 and there is general consensus of the importance of early referral for pre-ESRD care. [22][23][24][25][26][27] Although many AVFs are created in advance of dialysis initiation, 99% of fistulae were cannulated within 4 months of their creation in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Most experts advocate early placement of AVFs considering that fistulae need about 4-6 weeks to mature for use, 20,21 and there is general consensus of the importance of early referral for pre-ESRD care. [22][23][24][25][26][27] Although many AVFs are created in advance of dialysis initiation, 99% of fistulae were cannulated within 4 months of their creation in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…We continue to believe, however, that a randomized study examining this issue is desperately needed. At present, there are no effective pharmacologic treatments to promote AVF maturation, largely due to our limited understanding of the pathophysiology of AVF maturation (1)(2)(3)17,44,45). In this regard, a large randomized, double-blinded clinical trial found that clopidogrel significantly reduced early AVF thrombosis but failed to decrease AVF nonmaturation (14).…”
Section: Discussionmentioning
confidence: 99%
“…The histology of AVF nonmaturation has been demonstrated to be secondary to aggressive venous neointimal hyperplasia ( Figure 2, A and B), with the majority of cells within the neointima staining for myofibroblasts, but with contractile smooth muscle cells and fibroblasts also present (6). In addition to aggressive neointimal hyperplasia development, inadequate vasodilation (inward remodeling), resulting in vasoconstriction of the vein, also likely plays an important role in AVF nonmaturation (7)(8)(9)(10).…”
Section: Histopathology Of Hemodialysis Vascular Access Dysfunction Avfsmentioning
confidence: 99%